Examining human-animal interactions and their effect on multidimensional frailty in later life: a scoping review - Taeckens, Ashley; Corcoran, Mary; Wang, Kaipeng; Morris, Kevin N. (Frontiers in Public Health, 2023)
This scoping review sought to compile outcomes associated with any human-animal interaction study regarding adults aged 50 and older in any living context and concerning a multidimensional (i.e., physical, psychological, cognitive, and social) perspective of frailty. Despite our best attempts at incorporating the broadest inclusion criteria possible, only four articles were relevant to this review. Participants across the included studies were rural, community-dwelling Japanese or Chinese individuals aged 60 years and older. Thematic analysis of reported results includes dog ownership as a protective factor regarding frailty, the interconnected health effects of pet ownership, and increased meaning and purpose through pet ownership implications. More research is needed globally to determine how human-animal interactions may moderate frailty comprehensively, as well as the efficacy and appropriateness of these interactions or interventions in older adult populations and across cultural boundaries.